Prehistoric Pendants as Instigators of Sound and Body Movements : A Traceological Case Study from Northeast Europe, c. 8200 cal. BP - Rainio, Riitta; Gerasimov, Dmitrij V.; Girya, Evgeny; Mannermaa, Kristiina (Cambridge Archaeological Journal, 2022)
In the Late Mesolithic graves of Yuzhniy Oleniy Ostrov, Northwest Russia, large amounts of Eurasian elk (Alces alces) incisors have been found. These teeth, for the most part fashioned into portable pendants, seem to have formed decorative sets for the garments or accessories of the deceased. This article examines both the technologies associated with these artefacts and their uses, as well as reflecting on the sensorial experiences generated by them. Osteological analysis of a sample of 100 specimens indicates that all types of incisors were used for making the pendants. Traceological analysis indicates that the teeth were modified by scraping, grooving, grinding, and retouching. Traces of wear consist of general wear and distinctive pits or pecks on the perimeters of the crowns. These traces indicate that the pendants were worn before their deposition in the graves, in such a way that they were in contact with both soft and solid materials. The pattern of pits or pecks has until now been unreported in the traceological literature. In experiments, a similar pattern emerged when pendants of fresh elk incisors were hung in rows and bunches and struck against one another. These strokes created a rattling sound. Thus, the elk incisors of Yuzhniy Oleniy Ostrov appear to provide insight into previously unattainable sonic experiences and activities of Mesolithic hunter-gatherers, as well as the early history of the instrument category of rattles. Peer reviewed